The adult psychotherapy progress notes planner - Jongsma, Arthur E. Jr. 1943- (Practice planners., 2006)
As with the previous edition, The Adult Psychotherapy Progress Notes Planner, Third Edition helps mental health practitioners reduce the amount of time spent on paperwork by providing a full menu of pre-written progress notes that can be easily and quickly adapted to fit a particular patient need or treatment situation.